The Implementation Surveillance of Malaria at Kabawo Community Health Service Muna Regency - Nur Juliana; Firnasrudin Rahim; Harnianti (Politeknik Karya Persada Muna, 2021)
Baground: Malaria as an infectious disease caused by parasites of plasmodium and transmitted by anopheles mosquitoes, Data at Kabawo community health service an Annual Parasite Incidence 48,90‰ in 2016 year. This research obtained to get information the implementation of malaria surveillance. Method: This study applied qualitative design with a case study approach. Techniques of data collection used in-depth interviews, observations and document observations. Results: The results showed implementation of malaria surveillance included data collection from pustu, disease data, laboratories. Processing of data manually with the format data in the form of tables and graphs, but reports have not carried out on mapping areas of malaria cases. Analysis and interpretation of data includes people, time, and place to disease and trends based on monthly and yearly data. The distribution of data to sent with reporting, but the utilization of technology has not been fully carried out considering that still done manually. Feedback was done each programmer. Investigations were not carried out, only data collection and laboratory. Management through prevention with counseling and treatment. Evaluation through as mini workshop activities, has not been effective because of obstacles that hinder the implementation of activities. Conclusions: Data collection from disease reports, manual data processing, analysis using number calculations and interpretations comparing monthly and annual. Dissemination of information used was reporting, feedback on activities from each programmer, investigation of laboratory examinations and services to sufferers, prevention efforts through counseling and evaluation through mini workshops. Keywords: Surveillance, malaria disease, at kabawo community health service Pendahuluan: Malaria sebagai penyakit infeksi yang disebabkan oleh parasit Plasmodium dan ditularkan oleh nyamuk Anopheles, Data Puskesmas Kabawo Annual Parasite Incidence 48,90‰ tahun 2016. Penelitian ini bertujuan untuk memperoleh informasi tentang pelaksanaan surveilans penyakit malaria. Metode: Penelitian ini menggunakan penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data menggunakan wawancara mendalam, observasi dan pengamatan dokumen. Hasil: Hasil penelitian menunjukkan pelaksanaan surveilans malaria meliputi pengumpulan data dari Pustu, data penyakit, laboratorium. Pengolahan data secara manual dengan format penyajian data tabel dan grafik, namun laporan belum dilakukan pada pemetaan wilayah kasus penyakit malaria. Analisis dan interpretasi data meliputi orang, waktu, dan tempat sesuai penyakit dan trend berdasarkan data bulanan dan tahunan. Penyebaran data dikirim secara tertulis melalui pelaporan, akan tetapi untuk pemanfaatan teknologi belum sepenuhnya dilakukan mengingat data yang dilakukan masih manual. Umpan balik dilakukan dari masing-masing petugas. Investigasi tidak dilakukan, hanya melalui pendataan dan pemeriksaan laboratorium. Penanggulangan kasus melalui penyuluhan dan pengobatan. Evaluasi melalui kegiatan mini lokakarya, evaluasi dilakukan belum efektif karena kendala yang menghambat pelaksanaan kegiatan. Kesimpulan: Pengumpulan data dari laporan penyakit, pengolahan data manual, analisis data perhitungan jumlah dan interpretasi membandingkan data bulanan dan tahunan. Diseminasi menggunakan pencatatan dan pelaporan, umpan balik dari kegiatan masing-masing petugas, investigasi pemeriksaan laboratorium dan pelayanan kepada penderita, upaya penanggulangan melalui penyuluhan dan evaluasi melalui mini lokakarya. Kata kunci: Surveilans, penyakit malaria, puskesmas kabawo